Correlates of Unmet Need for Modern Contraception Among Reproductive-Aged Women Involved in New York City Criminal Legal Systems - Melissa N. Slavin; Brooke S. West; Deanna Schreiber-Gregory; Frances R. Levin; Gina Wingood; Steve Martino; Golfo Tzilos Wernette; Chermaine Black; Nabila El-Bassel (Women's Health Reports, 2024)
Introduction: The population of women involved in criminal legal systems (WICL), a majority of whom are reproductive-aged, has risen steadily in the United States. They contend with numerous barriers to sexual and reproductive health services resulting in high rates of unmet need for contraception and unintended pregnancy. Materials and Methods: This study included 132 non-pregnancy seeking reproductive-aged WICL enrolled in the baseline assessment of the HIV prevention intervention, ?Women on the Road to Health? (WORTH). A multivariate generalized linear logistic regression model with robust estimation examined effects of past 6-month intimate partner violence (IPV; sexual and physical/injurious), past 3-month substance use (binge drinking, cannabis, other illegal drug use), and lifetime mental health diagnoses (anxiety, depression, bipolar disorder) on women's unmet need for modern contraception, adjusting for significant demographic and socioeconomic factors. Results: Women who were younger in age (odds ratio [OR]: 0.74; 95% confidence interval [CI]: 0.63?0.88) and reporting lifetime diagnoses of anxiety disorders (OR: 13.64; 95% CI: 2.71?68.34) were significantly more likely to meet the criteria for unmet need for modern contraception. Women with a regular gynecologist (OR: 0.11; 95% CI: 0.01?0.86) reporting lifetime diagnoses of bipolar disorder and past 6-month sexual IPV histories (OR: 0.04; 95% CI: 0.002?0.86) were significantly less likely to meet the criteria for unmet need for modern contraception. Conclusions: Distinct mental health diagnoses and experiences of IPV may uniquely impact unmet need for modern contraception among WICL. These findings emphasize the need for a more nuanced comprehension of these relationships to deliver comprehensive and holistic health services that address the intersecting needs of this population. Trial registration: ClinicalTrials.gov NCT01784809. Registered 6 February 2013.